The distinct effects of aspirin on platelet aggregation induced by infectious bacteria. (16th November 2020) - Hannachi, Nadji; Baudoin, Jean-Pierre; Prasanth, Arsha; Habib, Gilbert; Camoin-Jau, Laurence
Abstract: Bacteria induce platelet aggregation triggered by several mechanisms. The goal of this work was to characterize platelet aggregates induced by different bacterial strains and to quantify the effect of aspirin treatment using aggregation tests, as well as a novel approach based on confocal analysis. Blood samples were obtained from either healthy donors (n = 27) or patients treated with long-term aspirin (n = 15). The bacterial species included were Staphylococcus aureus, Enterococcus faecalis, and Streptococcus sanguinis . The different aggregate's ultrastructures depending on the bacterial strain were analyzed using Scanning electron microscopy. Quantification of the size of the platelet aggregates, their mean number as well as the bacterial impregnation within the aggregates was performed using confocal laser scanning light microscopy. Light Transmission Aggregometry was also performed. Our results reported distinct characteristics of platelet aggregates depending on the bacterial strain. Using confocal analysis, we have shown that aspirin significantly reduced platelet aggregation induced by S. aureus ( p = .003) and E. faecalis ( p = .006) with no effect in the case of S. sanguinis ( p = .529). The results of the aggregometry were concordant with those of the confocal technique in the case of S. aureus and S. sanguinis . Interestingly, aggregation induced by E. faecalis was detected only with confocal analysis. In conclusion, our confocal scanning microscopy allowed a detailed study of the platelet aggregation induced by bacteria. We showed that aspirin acts on bacterial-induced platelet aggregation depending on the species. These results are in favor of the use of aspirin considering the species and the bacterial strain involved.